Grief Support and Coping Mechanism Mediate the Effect of Grief on Burnout Among Intensive Care Unit Nurses: A Structural Equation Modeling Analysis - Gurbinder Kaur, Jit Singh; Low, Wah Yun; Khatijah Lim, Abdullah * (Lippincott, Williams & Wilkins, 2023)
Background: Patients' death caused the intensive care unit (ICU) nurses to grieve, which led to their burnout. Intensive care unit nurses use various coping mechanisms and need support to overcome grief.